The Influence of Competency, Organizational Culture and Emotional Intelligence on the Performance of Hospital Electromedical Staff in Yogyakarta During the Pandemic - Budi Ramadianto; Nur Wening; Marwan Marwan (Dinasti International Journal of Education Management And Social Science, 2024)
The research aimed to determine the influence of competence, organizational culture, and emotional intelligence on the performance of hospital electromedical staff in Yogyakarta during the pandemic. The research used quantitative research. Quantitative research is a method based on the philosophy of positivism. The types of data of the research were primary and secondary. The population was approximately 100 Indonesian hospital electromedical staff in Yogyakarta. The tests for the instrument were validity and reliability tests, classical assumption tests (normality test, multicollinearity test, and heteroscedastic test), multiple linear regression analysis, and hypothesis test (t-test, R square coefficient test). The study showed that: 1) competency has a significant positive effect on the performance of hospital electromedical staff in Yogyakarta. 2) organizational culture has a significant positive effect on the performance of hospital electromedical staff in Yogyakarta. 3) emotional intelligence has not significant positive effect on the performance of hospital electromedical staff in Yogyakarta.